A Longitudinal Study on Adherence to Anti Retroviral Therapy and Its Determinants in Telangana State - Misha Gorantla; Varun M Malhotra; Nagaraj Kondagunta (Medsci Publications, 2019)
Introduction: India is among the list of countries with highest HIV prevalence. Adequate viral suppression requires strict adherence  to antiretroviral therapy (ART). This research was conducted to study the clinico-demographic profile of study population and to study the barriers to treatment adherence. Methodology: This is an observational follow up (longitudinal) study done on 142 patients which included all newly diagnosed, sero positive, adult patients, enrolled at an ART centre and started on treatment during the months of December 2012, January 2013, February 2013, using a pre designed, pre tested questionnaire. They were visited again after a year and adherence was calculated and determinants of adherence were studied. Results: After one year 129 patients remained, of which 49.61% pa- tients had good adherence and 50.39% patients had poor adherence. Risk factors associated with poor adherence were male sex, urban residence, lower socio economic status, illiteracy, un- skilled occupation, spouse negative for HIV, addictions like alco- holism, smoking, experience of drug side effects, early WHO clini- cal stage, low BMI, opportunistic infections and depression. Conclusion: There are many risk factors for non adherence many of which are preventable but are not emphasized in the national programme. National programmes must take these into account to strengthen HIV care.